2021
DOI: 10.3390/genes12050776
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Pre-Exposure May Differentially Modulate Plant Defense to Powdery Mildew in a Resistant and Susceptible Barley Genotype

Abstract: Heat stress negatively affects barley production and under elevated temperatures defense responses to powdery mildew (Blumeria graminis f. sp. hordei, Bgh) are altered. Previous research has analyzed the effects of short-term (30 s to 2 h) heat stress, however, few data are available on the influence of long-term exposure to heat on powdery mildew infections. We simultaneously assessed the effects of short and long term heat pre-exposure on resistance/susceptibility of barley to Bgh, evaluating powdery mildew … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Importantly, in our assays, we used intact barley plants as opposed to the experiments of Schwarzbach [ 26 ], where leaf segments were placed on agar medium, a likely cause of differential reactions of heat-stressed barley (35–36 °C for 1 and 2 h) to Bgh in the susceptible line. Recently, we found that prolonged heat stress pre-exposure (35 °C for 24, 48, and 120 h) confers enhanced susceptibility to Bgh in a susceptible barley line, while a resistant line retains its pathogen resistance [ 28 ]. Defense gene expression patterns following heat stress and Bgh inoculation were markedly different in the resistant and susceptible lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, in our assays, we used intact barley plants as opposed to the experiments of Schwarzbach [ 26 ], where leaf segments were placed on agar medium, a likely cause of differential reactions of heat-stressed barley (35–36 °C for 1 and 2 h) to Bgh in the susceptible line. Recently, we found that prolonged heat stress pre-exposure (35 °C for 24, 48, and 120 h) confers enhanced susceptibility to Bgh in a susceptible barley line, while a resistant line retains its pathogen resistance [ 28 ]. Defense gene expression patterns following heat stress and Bgh inoculation were markedly different in the resistant and susceptible lines.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze Bgh biomass, a protocol of reverse transcription followed by quantitative real-time polymerase chain reaction (RT-qPCR) was used as described previously for barley-Bgh and wheat- Puccinia striiformis f. sp. tritici interactions [ 28 , 69 ]. Collected leaf tissue was ground in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, rice frequently suffers from various biotic and abiotic stresses in nature [ 3 , 4 ]. As a consequence of global warming, the combination of pathogens and high temperatures (HT) frequently exists in the cultivation of cereal crops [ 5 , 6 , 7 , 8 ]. As the “cancer” of rice, M. oryzae is widely distributed, and terribly destructive under favorable conditions, which can cause severe yield losses in rice [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%